On Capital Productivity, Input Allocation and Growth - Bator, Francis M. (Quarterly Journal of Economics, 1957)
Introduction, 86. — I. The relation between “the” capital-output ratio, the marginal product of capital, and “the” interest rate, 86. — II. From the capital-output ratio and the interest rate to innovations by way of income-shares and factor-proportions, 93. — III. Choosing the input-mix: are capital-intensive processes desirable where capital is scarce relative to labor? 95. — IV. Some comments on difficulties with the capital-output ratio; on distribution, saving and input-allocation; on theorizing about allocation and growth, 101.